PENERAPAN UNIVERSAL PRECAUTION UNTUK PENCEGAHAN PENULARAN HIV-AIDS - Andriani, Lusi (JURNAL MEDIA KESEHATAN, 2014)
Universal Precaution socialization for midwives in Bengkulu had been realized since 2000 by giving preventive on infection (PI) information, but in fact UP implementation does not implemented properly so the risk of HIV & AIDS transmission becoming higher. The purpose of this research for analyze Universal Precaution practice by the midwives in delivery service for prevent HIV & AIDS transmission. This research is a part of explanatory research with cross sectional approaching. The sample of this research is the number of total population who included in the inclusion criteria, they are 220 midwives. The data collection was using questionnaire and for crosscheck data was using in-depth interview on 6 key informants. analyzing data using descriptive analysis and content analysis. There are five variables were giving the influences on this research, they are : the knowledge about HIV with OR=16.990, the knowledge on Universal Precaution with OR= 3.214, attitudes on HIV with OR=9.719, resources with OR= 28.416 and policy with OR= 4.847.